Départ d'un prophète, arrivée d'une Eglise. Textes et recherches sur la mort de Simon Kimbangu et sur sa survivance / Departure of a Prophet, Arrival of a Church. Texts and Research on the Death and Survival of Simon Kimbangu - Desroche, Henri; Raymaekers, Paul (Archives de Sciences Sociales des Religions, 1976)
The following dossier presents documents and studies relating to the death of the Congolese prophet Simon Kimbangu in 1951 after thirty years spent in prison, and his survival in the church bearing his name. The Authors' first concern is to shed light on the circumstances of S.K's death-bed "conversion" to catholicism, after he had been subjected to pressure from the prison administration. They next analyse the various aspects of the new "tolerance policy" which the Belgian administration applied after 1955 and which allowed and even encouragea the growth of the Kimbanguist Church under the leadership of one of the prophet's sons.
Free